ҚАРАҚАЛПАҚСТАНДАҒЫ АҢЫЗ-ӘПСАНАЛАР МЕНЕН БАЙЛАНЫСЛЫ АЙЫРЫМ ТОПОНИМЛЕР ҲАҚҚЫНДА - Кудиярова, Д. (ILIM hám JÁMIYET, 2018)
The article is devoted to the study of toponyms connected with mythology in Karakalpakstan. The materials of the article are important for Linguistics, History and Geography.